Open services innovation rethinking your business to grow and compete in a new era - Chesbrough, Henry William. (Jossey-Bass, 2011)
"The father of Open Innovation is back, this time with his most expansive, most significant book yet. Open Innovation described a new paradigm for the management of industrial innovation in the 21st century: How useful industrial knowledge today is widely distributed around the world and firms must open up to work with external partners to commercialize internal innovations, and allow unused internal ideas to be taken to market by others externally. Chesbrough's forthcoming Open Services Innovation demonstrates how the open innovation approach applies to companies both in the service businesses and those that want to be there. The book explains how companies must make two crucial shifts: one from products to services; and the other from closed to open innovation. Readers will discover: A competitive strategy and approach to business for today's services-based economy; A framework with guiding principles that will enable any business unit, company or industry to experience renewed growth and profits. Four new concepts are introduced and described in detail: Think of Your Business as a Services Business Co-Create with Customers and Partners Extend Services Innovation Outside Your Organization Transform Your Business Model with Services and Open Innovation Also learn about Services Innovation in Large and Smaller Companies, Open Services Innovation for Services Businesses, and Services Innovation in Emerging Economies Chesbrough enlightens his readers by explaining the need to develop a new perspective about business, one that rethinks the business models in a services-based economy. Chesbrough establishes that the future prosperity of companies comes from progressive shift to a largely services-based economy, driven by continued innovation. Chesbrough provides more than anecdotal material on how we must view industries, he leads us to examine how we do business. It is one thing to think of the automobile as a means for transportation, it's another to thing to provide transportation services over a life time"--